Jacquemontia verae (Convolvulaceae): a new species from Brazilian savannas - Pastore, Mayara; Moreira, André Luiz C.; Morais, Isa Lucia De; Romeiro, Luiza A.; Simão-Bianchini, Rosângela (Phytotaxa, 2025)
Jacquemontia verae is described as a new species from “cerrado rupestre” vegetation in the Cerrado biome of Goiás, Brazil. Line drawings and photographs illustrate the new species, including optical and scanning electron microscope images of pollen. It is compared morphologically with similar species of Jacquemontia and an identification key to species from the state of Goiás is provided. The conservation status of the new species is informally assessed as Critically Endangered (CR). Its relationships within Jacquemontia and its stigma structure are discussed.